The Immuno-Modulation Effect of Macrophage-Derived Extracellular Vesicles in Chronic Inflammatory Diseases - Xing, Yi; Sun, Xun; Dou, Yiming; Wang, Min; Zhao, Yanmei; Yang, Qiang; Zhao, Yanhong (Frontiers in Immunology, 2021)
As natural nanocarriers and intercellular messengers, the regulation of communications between cells can be controlled with exosomes. Under physiological or pathological conditions, exosomes deliver materials including proteins and nucleic acids to target cells, modulating the target cells. Macrophages-derived exosomes exert a vital influence on the development of chronic inflammations leading pathological changes above tissues and organs, and the biological functions and regulating effects of different phenotypes macrophages-derived exosomes on target cells always present different results with different type. In this review, we will describe the pathophysiological significance of macrophages-derived exosomes in the development of chronic diseases, including diabetes, cancer, cardiovascular diseases, pulmonary diseases and gastrointestinal diseases and their potential applications.